The customs in Xinjiang - Mamatniyaz, Gulbahar ("Charming Xinjiang" series, 2014)
The book delicately describes the splendid ethnic culture and impressive ethnic customs in the life of all ethnic groups in Xinjiang in layman's terms. Different styles of daily life, marriage, family, traditional but special life ceremony, hospitable folk customs, various festival traditions, colorful recreational activities as well as lively bazaar. The content and its illustrations are similarly excellent.